2011
DOI: 10.3109/17518423.2011.606509
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the validity of a structured interview protocol for assessing the preferences of children with autism spectrum disorders

Abstract: Results support the use of the structured interview protocol to determine the preferences of children with ASD. Practical implications and directions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…(2) Providing the child with choices (Tullis et al, 2011); for example, before the child goes to free play areas, the child can be provided with a choice of two or three items or activities. (3) Communication with the child’s family and educational team (Verschuur et al, 2011) about activities the child enjoys at home and educational contexts. Beyond these ideas, a formal preference assessment can be beneficial for identifying favorites (http://ebip.vkcsites.org/preference-assessments/ offers details and instructional videos of how to conduct a formal preference assessment).…”
Section: Using Aac To Support Communication—a Three-step Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Providing the child with choices (Tullis et al, 2011); for example, before the child goes to free play areas, the child can be provided with a choice of two or three items or activities. (3) Communication with the child’s family and educational team (Verschuur et al, 2011) about activities the child enjoys at home and educational contexts. Beyond these ideas, a formal preference assessment can be beneficial for identifying favorites (http://ebip.vkcsites.org/preference-assessments/ offers details and instructional videos of how to conduct a formal preference assessment).…”
Section: Using Aac To Support Communication—a Three-step Strategymentioning
confidence: 99%
“…(3) Communication with the child's family and educational team (Verschuur et al, 2011) about activities the child enjoys at home and educational contexts. Beyond these ideas, a formal preference assessment can be beneficial for identifying favorites (http://ebip.…”
Section: Step 1: Identify Preferred Activities/itemsmentioning
confidence: 99%
“…Most of these studies have found weak correspondence between caregiver or teacher-reported hierarchies and preference assessment hierarchies (Cote et al, 2007;Fisher et al, 1996;Green et al, 1991Green et al, , 1988Resetar & Noell, 2008). One exception, Verschuur et al (2011), found that an indirect assessment and an MSWO produced similar results. Some of these studies (Cote et al, 2007;Fisher et al, 1996;Resetar & Noell, 2008) have also conducted reinforcer assessments, which demonstrated that the stimuli identified as highly preferred by indirect and preference assessments were both likely to function as reinforcers.…”
mentioning
confidence: 99%
“…modes were assessed throughout each phase of the study. Based on previous research Piazza, Fisher, Hagopian, Bowman, & Toole, 1996;Verschuur et al, 2011), a structured choice-making paradigm was implemented to evaluate preferences for the three AAC modes. Specifically, the choice-making paradigm involved systematic presentation of discriminative stimuli (the AAC modes) and allowed individuals to retain use of the one AAC option that was selected (see Table 4.1 for an outline of the procedures).…”
Section: Methodsmentioning
confidence: 99%
“…As previously outlined (see Preference) a key component of the research was to promoteaspects of self-determination, in evident not only in terms of assessing which AAC option children preferred to use for requesting-based communication skills, but also in terms of assessing preferences to identify items that the children were taught to request. To this end, a systematic two-stage stimulus preference assessment Verschuur et al, 2011) was implemented to identify toys and/or snacks that participants appeared to prefer and would be appropriate to teach the requesting skills. Although some of the selection percentages for preferred stimuli could be interpreted as relatively low to be qualified as preferred (e.g., Study 1, playing on the computer = 30% for Zac), nearly all of the 12 participants consistently requested, selected, and then played with/consumed the toys or snacks identified through this process.…”
Section: Implications and Applicationsmentioning
confidence: 99%